Understanding Casual-leisure Information Behaviour - Max Wilson (Emerald, 2011)
Elsweiler, D., Wilson M. L. and Kirkegaard-Lunn, B. (to appear in 2011) Understanding Casual-leisure Information Behaviour. In Spink, A. and Heinstrom, J. (Eds) New Directions in Information Behaviour. Emerald. (Book Chapter)